A rare case report on esophageal squamous cell carcinoma metastatic to the pancreas - Bhatti, Inderpreet; Rogers, Robert E.; Witt, Benjamin L.; Nevala-Plagemann, Chris; Patterson-Fortin, Jeffrey (Frontiers in Oncology, 2025)
Pancreatic metastasis of esophageal squamous cell carcinoma is extremely rare. We describe a case of man aged 66 years who presented with a 3-month history of dysphagia. Esophagogastroduodenoscopy demonstrated an esophageal mass. Additional asymptomatic solitary lung and pancreatic masses were observed in the staging work-up for esophageal cancer, concerning for metastatic versus synchronous primary malignancy. Computed Tomography guided needle biopsy of the lung and pancreatic masses was performed. Given the difficulty to definitively histologically confirm both the lung and the pancreatic masses were metastasis from the primary esophageal cancer, next generation sequencing and tumor origin testing was performed. Tumor origin testing was indeterminate with the molecular profile inconclusive. Treatment was initiated with chemotherapy and immunotherapy.